AN EXPERIMENTAL STUDY ON THE CONSOLIDATION OF THE ATACK PHASE IN VOLEYBALL BY USING DINAMIC GAMES IN THE GYMNASIUM REPRESENTATIVE TEAM - BENEDEK FLORIAN; MIHALEA CRISTINA ELENA (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Volleyball is a collective sport which is practiced and appreciated by a large category of participants of all ages. Volleyball acquires certain characteristics, requirements and different purposes, depending on the participants' age. Using intensive means when teaching volleyball to students influences especially the motor qualities of students such as: force, speed, dexterousness and resistance, as well as some combined qualities. All of these qualities help to improve the physical education and the technicaltactic one. The physical education teacher or the coach must be informed and select as many dynamic games as possible, to be able to modify, direct and study them as well as to invent new ones if need it. I have personally chosen this theme because I have found it quite interesting and because the dynamic games are very widely spread and are often used as methods of physical education in many sportive fields. In my opinion, the dynamic games can consolidate the attack phase in volleyball especially in the gymnasium representative team.